2013
DOI: 10.1140/epje/i2013-13115-y
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial coherence length in a nematic π-cell

Abstract: In a highly frustrated calamitic nematic phase, the strain can be relaxed by lowering the nematic order: the starting uniaxial symmetry can be broken and it can be replaced locally with transient biaxial domains. Using simple optical retardation measurements, we estimate the length scale over which the biaxial disturbance decays in space within a π-cell submitted to a weak electric field. We also characterise the transition cascade from the uniaxial splay texture to a bend texture through slow defect motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Secondly, our model predicts that the WORS is observable for R ∼ 3.28ξ b is typically tens of nanometre [11]. Recent experimental work in a π -cell geometry, with conventional optical microscopy techniques, suggests that ξ (0) b ∼ 33 ± 9 nm [19]. This would correspond to cell sizes, R ∼ 78 − 138 nm, and such dimensions are widely modelled by LdG approaches in the community.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Secondly, our model predicts that the WORS is observable for R ∼ 3.28ξ b is typically tens of nanometre [11]. Recent experimental work in a π -cell geometry, with conventional optical microscopy techniques, suggests that ξ (0) b ∼ 33 ± 9 nm [19]. This would correspond to cell sizes, R ∼ 78 − 138 nm, and such dimensions are widely modelled by LdG approaches in the community.…”
Section: Resultsmentioning
confidence: 75%
“…The same temperature was chosen in [22], where the authors study OR patterns in 'classical' hybrid planar cells. In dimensional terms, this would correspond to a well with R ∼ 120-150 nm [19]. The Dirichlet conditions (see (3.7) and (3.8)) induce an alignment mismatch along the four vertical edges and, consequently, we obtain four line defects along the four vertical edges in the z-direction.…”
Section: Macroscopic Wells Withmentioning
confidence: 91%
See 1 more Smart Citation
“…The top cell view is presented and disclinations are visualized by plotting regions of relatively strongly suppressed order parameter, which is realized in the cores of defects. The thickness of disclination lines is roughly given by the nematic biaxial correlation length [7,44] The free energies F of the patterns are, in general, different and depend on geometry and LC material properties. For example, for the set of parameters h ξ b = d ξ b = 50, a strong anchoring condition at the master plate and an absence of an external electric field, the excess free energy F [pattern] = F − F n of all patterns is roughly the same (their values differ for less than 1%), where F n determines the free energy of the equilibrium bulk nematic.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The scale over which biaxial order extends in a uniaxial medium Downloaded by [University of Sussex Library] at 23:51 18 August 2015 is known as biaxial coherence length and denoted by ξ b [12]. A dynamical numerical model has shown that ξ b ∼ 5 nm for 5 CB close to the nematic-isotropic transition [13] and recent measurements in the π -cell have given ξ b ∼ 30 nm for 5 CB at T = 25 • C [14]. These experimental values are presumably overestimated because of the simplified optical model adopted to extrapolate ξ b , therefore at present the best value for ξ b is in the order of 5-10 nm.…”
Section: Introductionmentioning
confidence: 99%